The Effect of Leptin Hormone Levels In Type( II) Diabetic Nephropathy Patients - Taher, N. T. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Type 2 diabetes Nephropathy complication is one of the most commonest metabolic disorders that becomes an advanced serum level of hormone altered. The objective is to study the effect of leptin levels in Type 2 diabetes nephropathy (D.N) complication and healthy subject. This study was done in National Diabetes Center (NDC), AL-Mustansriya University;on a total (64) individuals whase age were ranged from(45-60) years,of which (38) patients of type 2 diabetes nephropathy, and (26) healthy( controls). The collected data ,information concerning the individuals used in the present study were: age, sex , body mass index (BMI) and blood samples to estimate serum leptin levels , fasting plasma glugcose (FPG) , glycated hemoglobin (HbA1c), serum creatinine, blood urea , and micral tests (urinary to microalbumine to creatinine ratio). The mean FPG, HbA1c and Micral tests of type 2 diabetes nephropathy (D.N) showed statistical significant with healthy control ;on the other hard the data shows significant increases in leptin level in type 2 diabetes nephropathy (D.N) ( urinary microalbumin to creatnin ratio ranged 30-300 mg/g) compared with healthy control. No significant correlation was present between serum leptin and both serum creatinine and blood urea ,so there wasn’t any correlation between BMI and serum leptin levels .In conclusion the results showed that serum leptin level was elevated in type 2 diabetes nephropathy(D.N) because impaired increase with progression of renal disease in diabetic nephropathy.